Carbon intensity of mass timber materials: impacts of sourcing and transportation - Atnoorkar, Swaroop; Ghatpande, Omkar A.; Haile, Selam L.; Goetsch, Heather E.; Harris, Chioke B. (Frontiers in Built Environment, 2024)
Mass timber construction is widely considered a promising alternative construction method to reduce buildings' total life-cycle carbon emissions because wood is a carbon sink. clt panels, manufactured by gluing lumber layers with grains at right angles, are potential low-carbon alternatives to carbon-intensive concrete and steel construction. However, most environmental impact assessment studies do not consider variation in transportation impacts within the clt supply chain when calculating life-cycle impacts. This study investigates the embodied primary energy and the gwp of clt supply chain decisions regarding the type of timber species used, the U.S. region it is sourced from, and the location of the clt mill. Longer transport distances in the supply chain for timber and clt panels can contribute as much as 923 MJ/m2 (20%) of the embodied primary energy of a clt building, and the use of a higher-density timber species increases this contribution to 1246 MJ/m2 (24%), with most of that energy derived from fossil energy sources. For perspective, the gwp of a building whose clt panels and timber have been transported by truck over 6,000 km (252–270 kgCO2/m2) is greater than the gwp of an equivalent rc building (245 kgCO2/m2). Thus, factors like the location of clt processing facilities and the type of timber species can significantly impact the overall life-cycle assessment and, if chosen appropriately, can mitigate the environmental impacts of clt construction.